ASSESSMENT OF THE PARAMETERS OF THE INTEROCCLUSION RELATIONSHIP IN THE PROCESS OF MESIALIZATION OF THE LOWER MOLARS WITH THE USE OF T-SCAN - V.S. Melnyk; O.Yu. Rivis; L.F. Horzov; M.V. Rivis; Yu.M. Bun (Український стоматологічний альманах)
The aim of the study. Conduct a digital analysis of the distribution of relative force occlusal load in the area of the second permanent mandibular molars before and after their mesialization.